Fusiform micro-nano hierarchical structure TATB crystal and preparation method thereof

The spindle-shaped micro-nano-classified TATB crystals were prepared by solvothermal method, which solved the problem of optimal orientation of TATB crystal particles and achieved better explosive performance.

CN119661373APending Publication Date: 2025-03-21INST OF CHEM MATERIAL CHINA ACADEMY OF ENG PHYSICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411769241.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art is difficult to reduce the preferred orientation of its particles through the regulation of TATB crystal morphology, affecting the use of explosives.

Method used

By using a one-step solvothermal method, a spindle-shaped micro-nano-classified TATB crystal was prepared by mixing TATB powder with the solvent at room temperature, and then dispersing ultrasonically, and then solvothermal reaction was carried out in an autoclave to regulate the reaction temperature, time and cooling rate.

Benefits of technology

A spindle-shaped micro-nano-classified TATB crystal with an average particle size of 15-60 μm and an average ellipticity of 0.40-0.70 was successfully prepared, which reduced the optimal orientation of the crystal particles and improved the use performance of explosives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661373A_ABST
    Figure CN119661373A_ABST
Patent Text Reader

Abstract

The invention discloses a fusiform micro-nano hierarchical structure TATB crystal and a preparation method thereof.The fusiform micro-nano hierarchical structure TATB crystal is prepared through a one-step solvothermal method, and the preparation method specifically comprises the steps that a TATB powder raw material and a solvent are mixed at room temperature and subjected to ultrasonic dispersion, and a TATB mixed solution is obtained; and transferring the TATB mixed solution into a high-pressure reaction kettle, carrying out solvothermal reaction, cooling to room temperature after the reaction is finished, taking out a product, filtering, washing and drying to obtain the fusiform micro-nano hierarchical structure TATB crystal. According to the preparation method, the technological process is simple, and the prepared fusiform micro-nano hierarchical structure TATB crystal is formed by directionally assembling nanocrystals and is good in free-running property and high in bulk density, so that the layered stacking characteristic of the TATB crystal is changed, and the preferred orientation of crystal particles can be reduced; the average particle size range of the TATB crystal is 15-60 [mu] m, and the average ovality of the TATB crystal is 0.40-0.70.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of energetic materials, and in particular to a TATB crystal with a spindle-shaped micro-nano hierarchical structure and a preparation method thereof. Background Art

[0002] 1,3,5-Triamino-2,4,6-trinitrobenzene (TATB) is currently the only single explosive that meets the standards for insensitive high-energy explosives. In recent years, polymer bonded explosives (PBX) based on TATB have been widely used in weapon charges. Currently, 1,3,5-Triamino-2,4,6-trinitrobenzene (TATB) used in charge is generally directly synthesized flaky particles with significant preferential orientation, which affects the use of explosives.

[0003] Recrystallization is one of the effective methods to control the morphology of explosive crystals. However, due to the special graphite-like layered structure of 1,3,5-triamino-2,4,6-trinitrobenzene (TATB) molecules, it is difficult to change the crystal layered stacking characteristics by ordinary recrystallization methods, and the problem of preferred orientation of recrystallized particles cannot be solved. Therefore, how to reduce the preferred orientation of particles by regulating the morphology of TATB crystals is a key issue that needs to be solved urgently. Summary of the invention

[0004] The purpose of the present invention is to provide a spindle-shaped micro-nano hierarchical structure TATB crystal and a preparation method thereof, in order to solve the technical problems existing in the background technology.

[0005] The present invention solves the above problems through the following technical solutions:

[0006] A method for preparing a spindle-shaped micro-nano hierarchical structure TATB crystal is provided, wherein a spindle-shaped micro-nano hierarchical structure TATB crystal is prepared by a one-step solvothermal method, and specifically comprises the following steps:

[0007] (1) mixing TATB powder raw material and solvent at room temperature, and ultrasonically dispersing them to obtain a TATB mixed solution;

[0008] (2) transferring the TATB mixed solution into a high-pressure reactor to carry out a solvothermal reaction. After the reaction is completed, the solution is cooled to room temperature, the product is taken out, filtered, washed and dried to obtain the spindle-shaped micro-nano hierarchical structure TATB crystal.

[0009] As a further improvement, the solvent is any one or more of an organic solvent or an ionic liquid.

[0010] As a further improvement, the organic solvent is dimethyl sulfoxide (DMSO) or N,N-dimethylformamide (DMF); and the ionic liquid is an imidazole ionic liquid.

[0011] As a further improvement, the imidazole ionic liquid is 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium nitrate, 1-ethyl-3-methylimidazolium acetate, 1-ethyl-3-methylimidazolium bicarbonate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium nitrate, 1-butyl-3-methylimidazolium acetate, 1-butyl-3-methylimidazolium bicarbonate, 1-allyl-3-ethylimidazolium tetrafluoroborate, or 1-vinyl-3-ethylimidazolium tetrafluoroborate. As a further improvement, the mass ratio of the TATB powder raw material to the solvent is 0.01 to 0.2.

[0012] As a further improvement, the temperature of the solvent thermal reaction is 100-160°C.

[0013] As a further improvement, the solvent thermal reaction time is 5 to 60 hours.

[0014] As a further improvement, the cooling rate is 0.01°C / min to 0.1°C / min.

[0015] In addition, the present invention also solves the above-mentioned problem through the following technical solutions:

[0016] A spindle-shaped micro-nano hierarchical structure TATB crystal is produced by the above-mentioned spindle-shaped micro-nano hierarchical structure TATB crystal preparation method; the spindle-shaped micro-nano hierarchical structure TATB crystal has an average particle size range of 15 to 60 μm and an average ellipticity of 0.40 to 0.70.

[0017] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0018] The preparation method of the present invention has a simple process flow. The prepared spindle-shaped micro-nano hierarchical structure TATB crystal is formed by directional assembly of nanocrystals, i.e., building units constituting the micro-nano hierarchical structure. It has good fluidity and high bulk density, thereby changing the layered stacking characteristics of the TATB crystal and reducing the preferred orientation of the crystal particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A schematic diagram of the spindle-shaped micro-nano hierarchical structure TATB crystal prepared by the present invention;

[0020] Figure 2 This is a locally enlarged SEM image of the spindle-shaped micro-nano hierarchical structure TATB crystal prepared in the present invention. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solutions and advantages of the present application clearer, the technical solutions in the embodiments of the present application will be described in more detail below in conjunction with the drawings in the preferred embodiments of the present application. In the drawings, the same or similar reference numerals throughout represent the same or similar parts or parts with the same or similar functions. The described embodiments are part of the embodiments of the present application, not all of the embodiments. The embodiments described below with reference to the drawings are exemplary and are intended to be used to explain the present application, and should not be construed as limitations on the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.

[0022] The embodiments of the present application are described in detail below with reference to the accompanying drawings.

[0023] See attached Figure 1-2 A spindle-shaped micro-nano hierarchical structure TATB crystal is formed by directional assembly of nanocrystals. The average particle size of the spindle-shaped micro-nano hierarchical structure TATB crystal ranges from 15 to 60 μm, and the average ellipticity is 0.40 to 0.70.

[0024] Accordingly, a method for preparing a spindle-shaped micro-nano hierarchical structure TATB crystal of the present invention is to prepare a spindle-shaped micro-nano hierarchical structure TATB crystal by a one-step solvothermal method, which specifically comprises the following steps:

[0025] (1) Mixing TATB powder raw material and solvent at room temperature, wherein the solvent is an ionic liquid, and ultrasonically dispersing to obtain a TATB mixed solution;

[0026] (2) transferring the TATB mixed solution into a high-pressure reactor to carry out a solvothermal reaction. After the reaction is completed, the solution is cooled to room temperature, the product is taken out, filtered, washed and dried to obtain the spindle-shaped micro-nano hierarchical structure TATB crystal.

[0027] Furthermore, the solvent is selected from any one or more of an organic solvent and an ionic liquid. Preferably, the organic solvent is dimethyl sulfoxide (DMSO) or N,N-dimethylformamide (DMF); and the ionic liquid is an imidazole ionic liquid.

[0028] More preferably, the imidazolium ionic liquid is 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium nitrate, 1-ethyl-3-methylimidazolium acetate, 1-ethyl-3-methylimidazolium bicarbonate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium nitrate, 1-butyl-3-methylimidazolium acetate, 1-butyl-3-methylimidazolium bicarbonate, 1-allyl-3-ethylimidazolium tetrafluoroborate, or 1-vinyl-3-ethylimidazolium tetrafluoroborate.

[0029] Preferably, the mass ratio of TATB powder raw material to solvent is 0.01-0.2; the temperature of the solvothermal reaction is 100-160° C.; the time of the solvothermal reaction is 5-60 h; and the cooling rate is 0.01° C. / min-0.1° C. / min.

[0030] The method for preparing spindle-shaped micro-nano hierarchical structure TATB crystals provided by the present invention has a simple process flow, and the spindle-shaped micro-nano hierarchical structure is prepared by a one-step solvent thermal method, wherein the particle size and ellipticity of the spindle-shaped micro-nano hierarchical structure are regulated by the solvent thermal reaction temperature, the solvent thermal reaction time and the cooling rate, so that the prepared crystal product is a spindle-shaped micro-nano hierarchical structure TATB crystal with an average particle size of 15 to 60 μm and an average ellipticity of 0.40 to 0.70.

[0031] The shuttle-shaped micro-nano hierarchical structure TATB crystal prepared by the present invention is reacted in a high-pressure container with the participation of a fluid. The prepared TATB crystal has a shuttle-shaped micro-nano hierarchical structure, which is different from the morphology of the TATB crystal prepared by the existing method and crystallized under normal pressure.

[0032] In some specific embodiments:

[0033] Example 1

[0034] 0.5 g of solid TATB powder raw material, 10 g of DMSO and 10 g of 1-ethyl-3-methylimidazole nitrate were mixed at room temperature. Ultrasonic dispersion was performed at 350 W for 30 minutes. After the end of the ultrasonication, the TATB mixed solution was transferred to a 25 mL autoclave and subjected to a solvothermal reaction at 100 ° C for 24 h. The product was then cooled to room temperature at 0.05 ° C / min, and the product was taken out, filtered, washed, and vacuum dried to obtain spindle-shaped micro-nano hierarchical structure TATB crystals with an average particle size of 20 μm and an average ellipticity of 0.45.

[0035] Example 2

[0036] 0.8 g of solid TATB powder raw material, 10 g of DMF and 8 g of 1-ethyl-3-methylimidazolium tetrafluoroborate were mixed at room temperature. Ultrasonic dispersion was carried out at 350 W for 30 minutes. After the end of the ultrasonication, the TATB mixed solution was transferred to a 25 mL autoclave and subjected to solvent thermal reaction at 120 ° C for 36 hours. Then, the product was cooled to room temperature at 0.02 ° C / min, and the product was taken out, filtered, washed, and vacuum dried to obtain spindle-shaped micro-nano hierarchical structure TATB crystals with an average particle size of 40 μm and an average ellipticity of 0.50.

[0037] Example 3

[0038] 1.0 g of solid TATB powder raw material and 15 g of 1-ethyl-3-methylimidazolium acetate were mixed at room temperature. Ultrasonic dispersion was performed at 350 W for 30 minutes. After the end of the ultrasonication, the TATB mixed solution was transferred to a 25 mL autoclave and subjected to a solvothermal reaction at 150 ° C for 40 h. The product was then cooled to room temperature at 0.05 ° C / min, and the product was taken out, filtered, washed, and vacuum dried to obtain spindle-shaped micro-nano hierarchical structure TATB crystals with an average particle size of 30 μm and an average ellipticity of 0.65.

[0039] Example 4

[0040] 1.0 g of solid TATB powder raw material and 20 g of 1-butyl-3-methylimidazole bicarbonate were mixed at room temperature. Ultrasonic dispersion was performed at 350 W for 30 minutes. After the end of the ultrasonication, the TATB mixed solution was transferred to a 30 mL autoclave and subjected to a solvothermal reaction at 140 ° C for 60 h. The product was then cooled to room temperature at 0.1 ° C / min, and the product was taken out, filtered, washed, and vacuum dried to obtain spindle-shaped micro-nano hierarchical structure TATB crystals with an average particle size of 35 μm and an average ellipticity of 0.60.

[0041] Example 5

[0042] 1.0 g of solid TATB powder raw material, 5 g of DMSO and 15 g of 1-allyl-3-ethylimidazolium tetrafluoroborate were mixed at room temperature. Ultrasonic dispersion was performed at 350 W for 30 minutes. After the end of the ultrasonication, the TATB mixed solution was transferred to a 30 mL autoclave and subjected to a solvothermal reaction at 120 ° C for 50 h. The product was then cooled to room temperature at 0.08 ° C / min, and the product was taken out, filtered, washed and vacuum dried to obtain spindle-shaped micro-nano hierarchical structure TATB crystals with an average particle size of 45 μm and an average ellipticity of 0.58.

[0043] Example 6

[0044] 0.1 g of solid TATB powder raw material and 10 g of DMSO were mixed at room temperature. Ultrasonic dispersion was performed at 350 W for 30 minutes. After the end of the ultrasonication, the mixed solution was transferred to a 25 mL autoclave and subjected to a solvothermal reaction at 100 ° C for 48 h. The product was then cooled to room temperature at 0.05 ° C / min, and the product was taken out, filtered, washed, and vacuum dried to obtain spindle-shaped micro-nano hierarchical structure TATB crystals with an average particle size of 15 μm and an average ellipticity of 0.50.

[0045] Example 7

[0046] 0.02 g of solid TATB powder raw material and 15 g of DMF were mixed at room temperature. Ultrasonic dispersion was performed at 350 W for 30 minutes. After the end of the ultrasonication, the mixed solution was transferred to a 25 mL autoclave and subjected to a solvothermal reaction at 100 ° C for 50 h. The product was then cooled to room temperature at 0.03 ° C / min, and the product was taken out, filtered, washed, and vacuum dried to obtain spindle-shaped micro-nano hierarchical structure TATB crystals with an average particle size of 18 μm and an average ellipticity of 0.52.

[0047] Example 8

[0048] 0.5 g of solid TATB powder raw material, 10 g of DMF and 15 g of 1-butyl-3-methylimidazole nitrate were mixed at room temperature. Ultrasonic dispersion was performed at 350 W for 30 minutes. After the end of the ultrasonication, the mixed solution was transferred to a 30 mL autoclave and subjected to solvent thermal reaction at 100 ° C for 5 h. Then, the mixture was cooled to room temperature at 0.01 ° C / min. The product was taken out, filtered, washed and vacuum dried to obtain spindle-shaped micro-nano hierarchical structure TATB crystals with an average particle size of 50 μm and an average ellipticity of 0.45.

[0049] Although the present invention is described herein with reference to the illustrative embodiments of the present invention, the above embodiments are only preferred embodiments of the present invention, and the embodiments of the present invention are not limited to the above embodiments. It should be understood that those skilled in the art can design many other modifications and embodiments, which will fall within the scope and spirit of the principles disclosed in this application.

Claims

1. A method for preparing spindle-shaped micro-nano hierarchical structure TATB crystals, characterized in that: A spindle-shaped micro-nano hierarchical structure TATB crystal is prepared by a one-step solvothermal method, which specifically includes the following steps: (1) mixing TATB powder raw material and solvent at room temperature, and ultrasonically dispersing them to obtain a TATB mixed solution; (2) transferring the TATB mixed solution into a high-pressure reactor to carry out a solvothermal reaction. After the reaction is completed, the solution is cooled to room temperature, the product is taken out, filtered, washed and dried to obtain the spindle-shaped micro-nano hierarchical structure TATB crystal.

2. The method for preparing a spindle-shaped micro-nano hierarchical structure TATB crystal according to claim 1, characterized in that: The solvent is any one or more of an organic solvent or an ionic liquid.

3. The method for preparing a spindle-shaped micro-nano hierarchical structure TATB crystal according to claim 2, characterized in that: The organic solvent is dimethyl sulfoxide (DMSO) or N,N-dimethylformamide (DMF); the ionic liquid is imidazole ionic liquid.

4. The method for preparing a spindle-shaped micro-nano hierarchical structure TATB crystal according to claim 3, characterized in that: The imidazolium ionic liquid is 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium nitrate, 1-ethyl-3-methylimidazolium acetate, 1-ethyl-3-methylimidazolium bicarbonate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium nitrate, 1-butyl-3-methylimidazolium acetate, 1-butyl-3-methylimidazolium bicarbonate, 1-allyl-3-ethylimidazolium tetrafluoroborate, or 1-vinyl-3-ethylimidazolium tetrafluoroborate.

5. The method for preparing a spindle-shaped micro-nano hierarchical structure TATB crystal according to claim 1, characterized in that: The mass ratio of the TATB powder raw material to the solvent is 0.01 to 0.

2.

6. The method for preparing a spindle-shaped micro-nano hierarchical structure TATB crystal according to claim 1, characterized in that: The temperature of the solvent thermal reaction is 100-160°C.

7. The method for preparing a spindle-shaped micro-nano hierarchical structure TATB crystal according to claim 1, characterized in that: The solvent thermal reaction time is 5 to 60 hours.

8. The method for preparing shuttle-shaped micro-nano hierarchical structure TATB crystal according to claim 1, characterized in that: The cooling rate is 0.01°C / min to 0.1°C / min.

9. A spindle-shaped micro-nano hierarchical structure TATB crystal, characterized in that: It is made by the method for preparing a spindle-shaped micro-nano hierarchical structure TATB crystal as described in any one of claims 1 to 8; The average particle size of the spindle-shaped micro-nano hierarchical structure TATB crystals ranges from 15 to 60 μm, and the average ellipticity ranges from 0.40 to 0.70.